2009
DOI: 10.1021/ic9018053
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Synthesis of Functionalized 1,3-Diphosphines via Chiral Palladium Complex Promoted Hydrophosphination of Activated Olefins

Abstract: Aldehyde, ester- and keto-functionalized monophosphine palladium complexes containing the ortho-metalated (R)-(1-(dimethylamino)ethyl)naphthalene as the chiral auxiliary and reaction promoter were synthesized via hydrophosphination of acrolein and the subsequent Wittig reactions in a one-pot process. Under very mild conditions, the second-stage hydrophosphination of the monophosphine substrates gave the corresponding ester-, keto-, and hydroxyl-functionalized chiral 1,3-bis(diphenylphosphino)propane palladium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
3

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…In the proposed mechanism the catalyst 55 acts as a base toward the diarylphosphine 25c . Some other examples of palladium-catalyzed asymmetric hydrophosphination are the addition of diphenylphosphine to α,β-unsaturated ketones [127128], esters [129], sulfonic esters [130] or to dienones [131]. The proposed mechanism is ubiquitous in metal-catalyzed hydrophosphination involving a P–H oxidative addition, insertion of the olefin into the Pd–H bond and reductive elimination.…”
Section: Reviewmentioning
confidence: 99%
“…In the proposed mechanism the catalyst 55 acts as a base toward the diarylphosphine 25c . Some other examples of palladium-catalyzed asymmetric hydrophosphination are the addition of diphenylphosphine to α,β-unsaturated ketones [127128], esters [129], sulfonic esters [130] or to dienones [131]. The proposed mechanism is ubiquitous in metal-catalyzed hydrophosphination involving a P–H oxidative addition, insertion of the olefin into the Pd–H bond and reductive elimination.…”
Section: Reviewmentioning
confidence: 99%
“…The best results were observed in the reaction of HPPh 2 with the simple symmetric enone 70a (entry 1). phosphines [53,54] and diphosphines [55][56][57][58]. The Leung group has reported a number of significant studies on the use of enantiopure cyclopalladated complexes as templates (auxiliaries) for asymmetric synthesis of compounds possessing ligand properties, e.g.…”
Section: Hydrophosphination Of -Unsaturated Carboxylic Acids Aldehmentioning
confidence: 99%
“…We had previously reported that orthometalated [1-(dimethylamino)­ethyl]­naphthalene palladium­(II) complexes and platinum­(II) complexes can act as a chiral template that promotes various reactions, namely, [4+2] cycloaddition, hydrophosphination, hydroamination, and hydroarsination reactions. , These reactions can generate many useful P -stereogenic phosphines under mild reaction conditions.…”
Section: Introductionmentioning
confidence: 99%